Disparities in the access to immune checkpoint inhibitors approved in the United States, the European Union and mainland China: a serial cross-sectional study - Jin-Ling Tang; Hao Hu; Carolina Oi Lam Ung; Shi-Yu Wang; Jia-Xin Cai; Fu-Xiao Li; Teng-Fei Lin; Shi-Fu Luo; Hai-Bo Song; Zhi-Rong Yang; Wei-Hua Meng (BMJ Public Health, 2025)
Background Immune checkpoint inhibitors (ICIs) have revolutionised antitumour therapy. However, regional differences in ICI labels, including the impact of the review process and supporting trial evidence, remain unclear.Methods We conducted a serial cross-sectional study to examine trends and differences in indication approvals and associated clinical trials for ICIs across different regulatory agencies. We searched ICI labels approved by the Food and Drug Administration (FDA), European Medicines Agency (EMA) and National Medical Products Administration (NMPA) in Mainland China before 31 December 2022 and assessed the indications and clinical trials in labels. Relative lags of indication approvals were compared using the Mann-Whitney U test. The review time and interval between trial completion and indication submission were compared using the Kruskal-Wallis test.Results We collected 10 ICIs with 90 indications from the FDA, 10 ICIs with 70 indications from EMA and 16 ICIs with 65 indications from NMPA. Relative lags of ICI indication approval in China (median 344.0 (IQR 220.0, 688.0) days) were longer than in the European Union (118.5 (55.0, 189.0) days) (p<0.0001). Both the European Union (243.0 (191.0, 298.0) days) and China (283.0 (248.0, 339.5) days) demonstrated significantly longer review durations for ICI indications than the United States (181.0 (148.8, 191.8) days) (p<0.0001). While indication submissions to NMPA were significantly more delayed than those to the FDA (p<0.001), the former relied more on trial evidence of OS (84.0%) than the latter (58.0%).Conclusion ICIs approved in the United States, the European Union and mainland China differed in indications, approval time, review duration and evidence base, which may impact access to life-saving treatments. Future studies should investigate the impact of these differences and the underlying reasons beyond the evidence supporting the label approvals.